Dietary Eucommia ulmoides Extract Alleviates the Effect of Cold Stress on Chick Growth Performance, Antioxidant and Immune Ability - Ting Hu (MDPI AG, 2021)
This study aimed to investigate the protective value of Eucommia ulmoides extract (EUE) on chicks under cold stress. A total of 21 compounds were identified in EUE using mass spectrometry (LC-MS). Ninety chicks were divided into a control group (CS) fed a basal diet and an experimental group supplemented with EUE, exposed to 10 ± 1 °C for 8 h per day. Results showed, compared with the CS group, the body weights (BW) (p < 0.01) and average daily gains ADG (p < 0.05) of the EUE group were increased throughout the study period. Chicks fed EUE had higher AFI (0–7 d, p < 0.001) and lower feed-to-gain ratios (F/G) (0–15 d, p < 0.001). EUE increased the activities of superoxide dismutase (SOD) (15 d, p < 0.05) and glutathione peroxidase (GSH-Px) (7 d, p < 0.05), whereas it decreased malondialdehyde (MDA) (15 d, p < 0.01). The contents of IgA (7 d, p < 0.05), IgG (7 d; 15 d, p < 0.01), and IgM (15 d, p < 0. 001) were higher in the EUE group. Dietary EUE could also reduce chick organ damage. Overall, EUE as a natural feed additive can improve the growth performance, antioxidant capacity, and immune level, and reduce the organ damage of cold-stressed chicks.